MANAJEMEN KESISWAAN PADA MADRASAH TSANAWIYAH NEGERI COT GUE KABUPATEN ACEH BESAR - Fadhilah .; Jamluddin Idris; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: The application of the student to the institution management is one of the necessity to improve the quality of education. Lack of school facilities and infrastructure become a major obstacle in the effective management of student affairs. This study aims to determine the planning, implementation, monitoring, and evaluation of student management program. The method used in this research is descriptive qualitative approach. Techniques of data collection : observation, interview and documentation. Subjects were principals, teachers and students MTsN Cot Gue. The results showed that : student management plan prepared by the principal with the deputy head of the student and deputy head of the curriculum includes courses Admission, the capacity of new students, and new student selection process, analyze subjects, draw up an annual program, the semester program, syllabus and Learning Program Plan. All the planning is composed arranged and documented. Implementation tailored to the student management plan that is prepared, either in relation to new admissions and student activities. Supervision of student management based on the management system, which is seeking any activities that have been planned, implemented and good supervision. Principals and teachers to supervise the implementation of student management. Both principals and teachers implement the roles and responsibilities based on the duties and functions for the management of student success. Activities and aspects of the management of student assessment based on the plans drawn up. The evaluation is done to see success and improve the activities that have been implemented.Keywords: Student Management, Islamic State Junior High SchoolAbstrak: Penerapan manajemen kesiswaan pada lembaga pendidikan merupakan salah satu keharusan untuk meningkatkan mutu pendidikan. Kurangnya sarana dan prasarana sekolah menjadi kendala yang utama dalam mengefektifkan manajemen kesiswaan. Penelitian ini bertujuan untuk mengetahui perencanaan, pelaksanaan, pengawasan, dan evaluasi program manajemen kesiswaan. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data: observasi, wawancara dan studi dokumentasi. Subyek penelitian adalah kepala sekolah, guru dan siswa MTsN Cot Gue. Hasil penelitian menunjukkan bahwa: perencanaan manajemen kesiswaan disusun oleh kepala sekolah bersama wakil kepala bidang kesiswaan meliputi program Penerimaan Siswa Baru, daya tampung siswa baru, dan proses seleksi siswa baru. Semua perencanaan tersusun disusun dan terdokumentasi. Pelaksanaan manajemen kesiswaan disesuaikan dengan perencanaan yang disusun, baik menyangkut dengan penerimaan siswa baru maupun kegiatan-kegiatan kesiswaan. Pengawasan manajemen kesiswaan berpedoman pada sistem manajemen, yaitu mengupayakan setiap kegiatan yang telah direncanakan, dilaksanakan dan pengawasan dengan baik. Kepala sekolah dan guru melakukan pengawasan terhadap penerapan manajemen kesiswaan. Baik kepala sekolah maupun guru melaksanakan peran dan tanggungjawabnya berdasarkan tugas pokok dan fungsinya untuk keberhasilan manajemen kesiswaan. Kegiatan dan aspek penilaian manajemen kesiswaan berpedoman pada rencana yang disusun. Evaluasi dilakukan untuk melihat keberhasilan dan memperbaiki kegiatan yang telah dilaksanakan.Kata Kunci: Manajemen Kesiswaan, Pada Madrasah Tsanawiyah Negeri